2008
DOI: 10.1029/2007jg000627
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the representativeness of the AmeriFlux network using MODIS and GOES data

Abstract: The AmeriFlux network of eddy covariance towers has played a critical role in the analysis of terrestrial water and carbon dynamics. It has been used to understand the general principles of ecosystem behaviors and to scale up those principles from sites to regions. To support the generalization from individual sites to large regions, it is essential that all major ecoregions in North America are represented in the AmeriFlux network. In this study, we examined the representativeness of the AmeriFlux network by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…An analysis of the monthly variations of the environmental variables revealed that the EVI had the largest variation, which is in accordance with the findings of Yang et al (2008). The great uncertainties in the EVI measurements indicated the potential of under-representation of the flux towers in terms of the vegetation types.…”
Section: Representativeness Of Different Vegetation Typessupporting
confidence: 86%
See 4 more Smart Citations
“…An analysis of the monthly variations of the environmental variables revealed that the EVI had the largest variation, which is in accordance with the findings of Yang et al (2008). The great uncertainties in the EVI measurements indicated the potential of under-representation of the flux towers in terms of the vegetation types.…”
Section: Representativeness Of Different Vegetation Typessupporting
confidence: 86%
“…The enhanced vegetation index (EVI) was selected because the vegetation physiological properties have an important effect on carbon exchange (Yang et al, 2008). The EVI is less sensitive to soil and atmospheric effects than the normalized difference vegetation index (NDVI) because it incorporates the blue spectral band.…”
Section: Selection Of the Environmental Variablesmentioning
confidence: 99%
See 3 more Smart Citations